2005
DOI: 10.1098/rspb.2004.2895
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear markers confirm taxonomic status and relationships among highly endangered and closely related right whale species

Abstract: Right whales (genus: Eubalaena) are among the most endangered mammals, yet their taxonomy and phylogeny have been questioned. A phylogenetic hypothesis based on mitochondrial DNA (mtDNA) variation recently prompted a taxonomic revision, increasing the number of right whale species to three. We critically evaluated this hypothesis using sequence data from 13 nuclear DNA (nuDNA) loci as well as the mtDNA control region. Fixed diagnostic characters among the nuclear markers strongly support the hypothesis of thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
42
3
5

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 96 publications
6
42
3
5
Order By: Relevance
“…However, in animals, too, the use of multiple nuclear markers as well as mitochondrial markers now is routine as demonstrated by recent studies of Drosophila (Ballard et al 2002;Kopp and Barmina 2005) and Hemiptera (Abe et al 2005), which show that nuclear and mitochondrial genes may support conflicting results. Nor is the use of PSR-GSC restricted to small animals, for example, a recent study of right whales found cryptic species, and in this case nuclear and mitochondrial genes were in agreement (Gaines et al 2005).…”
Section: Cryptic Speciesmentioning
confidence: 96%
“…However, in animals, too, the use of multiple nuclear markers as well as mitochondrial markers now is routine as demonstrated by recent studies of Drosophila (Ballard et al 2002;Kopp and Barmina 2005) and Hemiptera (Abe et al 2005), which show that nuclear and mitochondrial genes may support conflicting results. Nor is the use of PSR-GSC restricted to small animals, for example, a recent study of right whales found cryptic species, and in this case nuclear and mitochondrial genes were in agreement (Gaines et al 2005).…”
Section: Cryptic Speciesmentioning
confidence: 96%
“…Southern right whales are here considered as a distinct species, Eubalaena australis, following Rosenbaum et al (2000) and Gaines et al (2005).…”
Section: Taxonomymentioning
confidence: 99%
“…Analysis of genetic markers from both mitochondrial (Rosenbaum et al 2000) and nuclear DNA (Gaines et al 2005) indicate that right whales of the North Atlantic and of the Southern Hemisphere are 2 distinct species, Eubalaena glacialis and E. australis respectively. Genetic factors controlling fat storage and/or utilization may affect the observed difference in blubber thickness between the 2 species.…”
Section: North Atlantic Vs South African Right Whale Blubber Thicknessmentioning
confidence: 99%